(untitled) (Update Dental College Journal, 2022)
Gorlin-Goltz syndrome is an infrequent multisystemic disease with an autosomal dominant trait with complete penetrance and various expressivity. Gorlin Goltz Syndrome is a rare autosomal characterized by an increased predisposition to basal cell carcinoma and associated with multiorgan anomalies having a high level of penetrance. We report here a 60-year-old patient with positive findings of Gorlin-Goltz Syndrome.The following report emphasizes the identification of all the essential clinical diagnostic criteria ,radiological manifestations, and possible genetic tests to be performed for setting up an adequate treatment plan. Update Dent. Coll. j: 2022; 12(2): 32-36